Relationships Between Reaction Time, Selective Attention, Physical Activity, and Physical Fitness in Children - Reigal, Rafael E.; Barrero, Silvia; Martín, Ignacio; Morales-Sánchez, Verónica; Juárez-Ruiz de Mier, Rocío; Hernández-Mendo, Antonio (Frontiers in Psychology, 2019)
The objective of this study was to analyze the relationships between simple and complex reaction times (RTs) with the physical activity performed weekly, the physical fitness and selective attention in children of the third cycle of primary education. Participants were 119 children aged between 10 and 12 years (M = 10.71; SD = 0.77). The instruments used for data collection were the D2 attention test to analyze selective attention, various tests of the Eurofit and ALPHA-Fitness Battery to evaluate the physical condition, a bioimpedanciometer Tanita TBF 300 to evaluate the body composition, and the FITLIGHT Trainer to measure the simple and complex RTs. The group that carried out more weekly physical activity used less time in simple (p < 0.05, d = −0.68, 95% CI [−1.19, −0.17]) and complex RT tests (p < 0.05, d = −0.63, 95% CI [−1.14, −0.12]). Also, the results showed that the simple RT was related in a significant way with physical fitness, while the complex RT was related significantly to attentional capacity and physical fitness.